2015
DOI: 10.1007/s10389-015-0676-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association between pregnancy intention and insecticide-treated bed net (ITN) use: a cross-sectional study of pregnant women in Rwanda

Abstract: Aim To examine how pregnancy intention may be related to insecticide-treated bed net (ITN) use among pregnant women in Rwanda. Subject and methods This cross-sectional study applied random effects models to a nationally representative sample of pregnant women (n=837) from the 2010 Rwanda demographic and health survey (RDHS) who reported owning an ITN for their personal ownership and use at the time of the survey. Results The odds of reported ITN use the night before the survey are lower for women who reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Compared to women who did not want their pregnancies at all, women who wanted their pregnancies were more probable to use ITN. Women who become pregnant at the desirable time (planned) initiate have early and consistent ANC visits, adhere to health precautions and are health conscious [ 67 ]. Conversely, women whose pregnancies occurred later or earlier than planned (unintended) undergo heightened stress levels, which attenuates their prospects of undertaking healthy measures such as sleeping under ITNs [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to women who did not want their pregnancies at all, women who wanted their pregnancies were more probable to use ITN. Women who become pregnant at the desirable time (planned) initiate have early and consistent ANC visits, adhere to health precautions and are health conscious [ 67 ]. Conversely, women whose pregnancies occurred later or earlier than planned (unintended) undergo heightened stress levels, which attenuates their prospects of undertaking healthy measures such as sleeping under ITNs [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women who were not subscribed to health insurance were less probable to use ITN relative to those who had subscribed. To subscribe to health insurance is an indication of one’s consciousness and readiness to enjoy good health [ 67 ]. By inference, women who are subscribed to health insurance are sensitive to health issues and more conscious about the demerits of not using ITN compared with those who are not subscribed [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is however, noteworthy, that several other factors may contribute to less ITN use other than psychosocial distress and stress levels. In Rwanda, Thogarapalli et al [55] similarly observed that women with unintended pregnancies had reduced chances of utilizing ITNs. Women with unintended pregnancies in Nigeria may require further encouragement and education about ITN use.…”
Section: Discussionmentioning
confidence: 99%